สมบัติบางประการของจำนวนฟีโบนัชชี (p, q) และ จำนวนลูคัส (p, q) - จารุพร วางมือ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
In 2016, Gupta, Singh and Sikhwal [5] prove some properties of Fibonacci and Lucus numbers. Then in 2017, Pongsriiam [9] studied about the Diophantine equation of Fibonacci and Lucus numbers. Later, in 2017, Suvarnamani and Tatong [12] apply Binet’s formula to prove some properties of the product of (p, q) -Fibonacci and (p, q) -Lucus numbers. There are 4 objectives in this independent study. First, to study some properties of Fibonacci and Lucus numbers. Second, to study for finding the answer to the Diophantine equation of Fibonacci numbers and Lucus numbers. Next, to find some properties of (p, q) -Fibonacci and (p, q) -Lucus numbers. Last, to study for finding the answer to the Diophantine equation of (p, q) -Fibonacci numbers and (p, q) -Lucus numbers.